PENGEMBANGAN E-STORYBOOK BERBANTUAN CANVA DAN BOOK CREATOR PADA MATERI BENTANG ALAM INDONESIA SISWA KELAS III SEKOLAH DASAR - Eka Cecilia; Dwi Cahaya Nurani; Siti Dewi Maharani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop learning media in the form of E-Storybook with the help of Canva and Book Creator applications as two main applications in developing E-Storybook media on Indonesian landscape material for third grade elementary school students. This study uses the Research and Development method with the ADDIE model approach. Data analysis in the study was carried out by analyzing validity data and practicality data analysis. The validation results by the validator on the E-Storybook obtained a total score of 93.53%, the criteria of